1989
DOI: 10.1111/j.1600-0447.1989.tb01302.x
|View full text |Cite
|
Sign up to set email alerts
|

Psychotropic drug use in a representative community sample: the Upper Bavarian study

Abstract: A sample of 1979 community residents aged 15 years and above was assessed in a major survey of health status and consumption of psychotropic medication. Interviews were conducted in the subjects' home by a psychiatrically trained physician, who actually inspected the subjects' medical supplies. Of all subjects 6.9% (4.3% of the males and 9.0% of the females) had used a drug containing a benzodiazepine at least once in the 4 weeks preceding the interview. In the same period 3.6% had taken a medication containin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
16
0
2

Year Published

1998
1998
2006
2006

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(25 citation statements)
references
References 11 publications
7
16
0
2
Order By: Relevance
“…These studies have reported rates ranging from 27% to 60%, which are higher than the rates of 9.3 to 30.6% found in community studies. [7][8][9] Also, other previous studies 10, 11 have reported average numbers of psychotropic drugs prescribed that were similar to what was found in the present study.…”
Section: Discussionsupporting
confidence: 81%
“…These studies have reported rates ranging from 27% to 60%, which are higher than the rates of 9.3 to 30.6% found in community studies. [7][8][9] Also, other previous studies 10, 11 have reported average numbers of psychotropic drugs prescribed that were similar to what was found in the present study.…”
Section: Discussionsupporting
confidence: 81%
“…3,[29][30][31][32] This might be due to differences in method issues such as definition of psychotropic agents, data collection (eg, number of medications limited to 6 in this study), unit of observation, duration of data collection, and regional characteristics. Studies reporting sex and race information among elderly patients in the community receiving psychotropic agents concurred with our study's findings of greater prevalence among women 29,31,33,34 and whites.…”
Section: Commentmentioning
confidence: 99%
“…Most long-term tranquiliser users are women and elderly persons [2,6,[9][10][11]. In these cases BZDs tend to be prescribed mainly by general practitioners for sleep disorders, nervousness and, interestingly, physical diseases and chronic somatic complaints [3,10].…”
Section: Introductionmentioning
confidence: 99%
“…According to sales figures issued by the pharmaceutical industry, a considerable proportion of the population take BZDs over long periods, in many cases without an underlying medical indication, and may thus be regarded as potentially endangered by the consequences of longterm BZD use [7,8]. Most long-term tranquiliser users are women and elderly persons [2,6,[9][10][11]. In these cases BZDs tend to be prescribed mainly by general practitioners for sleep disorders, nervousness and, interestingly, physical diseases and chronic somatic complaints [3,10].…”
Section: Introductionmentioning
confidence: 99%